Everyday Meaning of Neighboring in Old Age in an Urban District. Issue 3 (2nd July 2020) - Seifert, Alexander; Schelling, Hans Rudolf
ABSTRACT: Contact and assistance between neighbors are prominent forms of social exchange in a spatial context. For older adults, the neighborhood gains in importance when mobility disabilities increase. This explorative study, therefore, aimed to investigate given and received neighborhood help and the everyday meaning of neighboring among older adults in an urban district. Study participants were aged 60 years and older (N = 100) living in an urban district of Zurich, Switzerland. Results highlight that older adults reported vivid interactions with their neighbors and that reciprocity exists between given and received neighborhood help. Besides that, daily contact and neighborhood help affect the perceived feeling of neighboring. Data indicate that neighboring is a meaningful resource for coping with everyday life situations in old age in an urban context.